Student Internship Admission Information System At Pt Pelabuhan Indonesia I Persero Belawan Branch - Desy Ramatika; Darmeli Nasution (Journal of Information Technology, computer science and Electrical Engineering, 2024)
PT Pelabuhan Indonesia I or often called Pelindo I is one of the State-Owned Enterprises of Indonesia engaged in the port services sector. The student internship acceptance system at PT Pelabuhan Indonesia Persero 1 Belawan Branch still uses a manual acceptance system and students must come directly to the location to apply for an internship. So that there are often obstacles experienced by students because most likely the company is not currently opening internship acceptance or if the company has run out of quota to accept internships because the quota has been fulfilled. Following up on the problems that occurred, a design for an intern acceptance information system was created. With the hope that this intern acceptance information system can solve existing problems. So that the acceptance of interns can be done easily without having to come directly to the company. This system is made using the PHP programming language which is website-based